2015
DOI: 10.1111/tbed.12320
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing of Bluetongue Viruses Isolated Over a Decade in South India

Abstract: Bluetongue (BT) is an arthropod-borne viral disease mostly of sheep. Bluetongue virus (BTV) is a segmented double-stranded RNA virus belonging to the genus Orbivirus of family Reoviridae and is transmitted by midges belonging to Culicoides spp. The disease is endemic in the tropics and subtropics, and the incidence is high in southern India. Twenty-six serotypes of BTV have been reported worldwide. Although most of the serotypes have been reported in India, information regarding currently circulating serotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Plaques can be seen as white areas. (Reddy et al, 2015) Identifying of plaques in the current study can be correlated with the observations of Howell et al, (1967) and Dulbecco (1952). The incubation time for plaque development is higher when compared with Cooper's (1962) study in which plaques were produced within 40 hrs of incubation.…”
Section: Molecular Confirmationsupporting
confidence: 90%
See 2 more Smart Citations
“…Plaques can be seen as white areas. (Reddy et al, 2015) Identifying of plaques in the current study can be correlated with the observations of Howell et al, (1967) and Dulbecco (1952). The incubation time for plaque development is higher when compared with Cooper's (1962) study in which plaques were produced within 40 hrs of incubation.…”
Section: Molecular Confirmationsupporting
confidence: 90%
“…Polymerase chain reaction for plaque purified virus was carried out with primers (IDT-DNA) specific for available bluetongue virus serotypes 2,4,9,10,12,16,21,23,24) (Reddy et al, 2015) along with positive and negative controls for each serotype.…”
Section: Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood samples from sheep showing BT‐like symptoms were collected from several outbreaks from different parts of Andhra Pradesh and Telangana states in South India, and virus isolation was accomplished by passaging the RBC lysates in KC cells followed by BHK‐21 cells. All the isolates ( n = 108) were tested by RT–PCR with primers against eight serotypes of BTV (BTV‐1, BTV‐2, BTV‐9, BTV‐12, BTV‐16, BTV‐21, BTV‐23, BTV‐24) circulating in India during the last decade (Krishnajyothi et al., ; Reddy et al., ). Sequence generated from one of the previously untyped virus isolates using next‐generation sequencing platform revealed that the isolate was related to BTV‐4 (Acc.…”
Section: Resultsmentioning
confidence: 99%
“…Although serotyping of BTV is based on the neutralization of virus using homotypic sera, typing based on reverse transcription–PCR and sequencing of seg‐2 is gaining popularity. However, nucleic acid sequences of seg‐2 of BTV isolated from different geographical areas differ significantly and the primers designed based on the reference viruses generally fail to detect different seg‐2 topotypes of the same serotype (Maan et al., , ; Mertens et al., ; Reddy et al., ). Hence, it is important to identify different topotypes and subtopotypes circulating in different geographical regions.…”
Section: Introductionmentioning
confidence: 99%